Role of Prophylactics Antibiotics in Clean Head and Neck Surgery in a Tertiary Care Center of Nepal: A Prospective Comparative Study - Paudel, Deepak; Karki, Anil Bikram; Shrestha, Amod (Journal of Nepal Health Research Council, 2024)
Background: Surgical site infections are well recognized complications of any surgical procedures. In head and neck surgeries, prophylactic antibiotics are commonly used to prevent Surgical site infections, in contaminated and clean contaminated procedures. Guidelines advised against routine antibiotics use in clean surgeries, but in our setting, non-compliance is frequent, resulting excessive antibiotics use. Objective of the study was to compare the Surgical site infections rate between prophylactics antibiotics group and no antibiotics group in clean head and neck surgery.Methods: It was a prospective comparative study conducted at a tertiary care centre of eastern Nepal. Patients were assigned to two groups, one receiving prophylactic antibiotics and another receiving no antibiotics.Results: Out of 131 patients, 66 received prophylactic antibiotics and 65 did not. Thyroidectomy was the most common surgery. The surgical site infection rate was 6.06% in antibiotic group and 7.69% in no antibiotic group, the difference was not significant (p=0.744). The risk reduction of surgical site infection with use of antibiotics was 0.0163 and number need to treat was calculated to be 61.35 About 3% of the patients who were administered antibiotics experienced adverse drug reactions. Factors, such as gender, amount of blood loss, smoking, placement of drains had no significant impact on Surgical site infections rate.Conclusions: Prophylactics antibiotics does not offer substantial advantages in preventing surgical site infections and are not advised for such procedures. Moreover, their use increases the financial burden and risk of adverse drug reactions to the patients. Keywords: Adverse drug reaction; antibiotics; surgical site infections; thyroidectomy.